Hematological Indices as Early Biomarkers of Diabetic Nephropathy - Sindhu S; Chitra Vellapandian (The Bioscan, 2026)
Diabetes mellitus is a chronic metabolic disorder characterized by persistent hyperglycemia resulting from defects in insulin secretion, insulin action, or both. Diabetic nephropathy (DN) is one of the most dangerous microvascular conditions that is linked to diabetes mellitus and is one of the major causes of end-stage renal disease on the international level.